Male Participation Factors in Antenatal Care for Maternal Health in Rural Areas: Systematic Review - Yolanda Safitri; Frima Elda (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Maternal health remains a critical global health priority, especially in rural areas where Antenatal Care (ANC) services often face significant challenges, including limited resources, low awareness, and cultural barriers. Male involvement plays a vital role in improving maternal health outcomes. This systematic review examines factors influencing male participation in ANC services in rural settings. A literature search was conducted using PubMed, ProQuest, and Scopus databases from 2019 to 2024. Keywords included